Quantification of Cardiac Kinetic Energy and Its Changes During Transmural Myocardial Infarction Assessed by Multi-Dimensional Seismocardiography - Morra, Sofia; Pitisci, Lorenzo; Su, Fuhong; Hossein, Amin; Rabineau, Jérémy; Racape, Judith; Gorlier, Damien; Herpain, Antoine; Migeotte, Pierre-François; Creteur, Jacques; van de Borne, Philippe (Frontiers in Cardiovascular Medicine, 2021)
INTRODUCTION Seismocardiography (SCG) records cardiac and blood-induced motion transmitted to the chest surface as vibratory phenomena. Evidences demonstrate that acute myocardial ischemia (AMI) profoundly affects the SCG signals. Multidimensional SCG records cardiac vibrations in linear and rotational dimensions and scalar parameter of kinetic energies can be computed. We speculate that AMI and revascularization profoundly modify cardiac kinetic energy as recorded by SCG. METHODS Under general anesthesia, 21 swines underwent 90 minutes myocardial ischemia induced by percutaneous sub occlusion of the proximal left anterior descending (LAD) coronary artery and subsequent revascularization. Invasive hemodynamic parameters were continuously recorded. SCG was recorded during the baseline; immediately and 80 min after LAD sub-occlusion; immediately and 60 min after LAD reperfusion. iK was automatically computed for each cardiac cycle (〖iK〗^CC) in linear (〖iK〗_Lin) and rotational (〖iK〗_Rot) dimensions. iK was calculated as well during systole and diastole (〖iK〗^Sys and 〖iK〗^Dia, respectively). Echocardiography was performed at the baseline and after revascularization and the left ventricle ejection fraction (LVEF) along with regional left ventricle (LV) wall abnormalities were evaluated. RESULTS Upon LAD sub-occlusion, 77% of STEMI and 24% of NSTEMI were observed. Compared to baseline, troponins increased from 13.0 [6.5; 21.3] ng/dL to 170.5 [102.5; 475.0] ng/dL and LVEF dropped from 65.0 ± 0.0% to 30.6 ± 5.7% at the end of revascularization (both p<0.0001). In the linear dimension, 〖iK〗_Lin^CC, 〖iK〗_Lin^Sys, 〖iK〗_Lin^Dia dropped by 43%, 52%, 53% respectively (p<0.0001, p<0.0001, p=0.03, respectively) from baseline to the end of reperfusion. In the rotational dimension, 〖iK〗_Rot^CC and 〖iK〗_Rot^Sys dropped by 30% and 36% respectively (p=0.0006 and p<0.0001, respectively), but 〖iK〗_Rot^Dia did not change (p=0.41). All the hemodynamic parameters, except the pulmonary artery pulse pressure, were significantly correlated with parameters of iK. CONCLUSIONS In this very context of experimental AMI with acute LV regional dysfunction and no concomitant AMI-related heart valve disease, linear and rotational iK parameters, in particular systolic ones, provide reliable information on LV contractile dysfunction and its effects on the downstream circulation. Multidimensional SCG may provide information on the cardiac contractile status expressed in term of iK during AMI and reperfusion.